ОРФОГРАФИЧЕСКАЯ РАБОТА В НАЧАЛЬНОМ КЛАССЕ - Лутфетдинова, Р.Х. (SCIENCE and SOCIETY, 2024)
The article is devoted to the specific features of the organization of preliminary work on spelling in classes with a multi-ethnic composition of students.